2014
DOI: 10.4102/ojvr.v81i1.679
|View full text |Cite
|
Sign up to set email alerts
|

Virulence of <i>Trypanosoma congolense</i> strains isolated from cattle and African buffaloes (<i>Syncerus caffer</i>) in KwaZulu-Natal, South Africa

Abstract: Trypanosoma congolense and Trypanosoma vivax are major species that infect cattle in north-eastern KwaZulu-Natal (KZN), South Africa. Of the two genetically distinct types of T. congolense, Savannah and Kilifi sub-groups, isolated from cattle and tsetse flies in KZN, the former is more prevalent and thought to be responsible for African animal trypanosomosis outbreaks in cattle. Furthermore, variation in pathogenicity within the Savannah sub-group is ascribed to strain differences and seems to be related to ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 26 publications
1
20
0
1
Order By: Relevance
“…Early isoenzyme analyses revealed three genetic variants or subgroups within T. congolense (Majiwa, Hamers, Van Meirvenne, & Matthyssens, ; Young & Godfrey, ). The most virulent and widespread is the Savannah subgroup, which is found in the savannah ecosystem and leads to anaemia, weight loss and usually death within three months postinfection (Bengaly, Sidibe, Boly, Sawadogo, & Desquesnes, ; Bengaly, Sidibe, Ganaba et al., ; Motloang, Masumu, Mans, & Latif, ). The two other subgroups comprise the low‐ and nonpathogenic Forest and Kilifi T. congolense parasites, respectively (Bengaly, Sidibe, Boly et al., ; Bengaly, Sidibe, Ganaba et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Early isoenzyme analyses revealed three genetic variants or subgroups within T. congolense (Majiwa, Hamers, Van Meirvenne, & Matthyssens, ; Young & Godfrey, ). The most virulent and widespread is the Savannah subgroup, which is found in the savannah ecosystem and leads to anaemia, weight loss and usually death within three months postinfection (Bengaly, Sidibe, Boly, Sawadogo, & Desquesnes, ; Bengaly, Sidibe, Ganaba et al., ; Motloang, Masumu, Mans, & Latif, ). The two other subgroups comprise the low‐ and nonpathogenic Forest and Kilifi T. congolense parasites, respectively (Bengaly, Sidibe, Boly et al., ; Bengaly, Sidibe, Ganaba et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…In South Africa, Glossina brevipalpis Newstead and Glossina austeni Newstead are the vectors of Trypanosoma congolense and Trypanosoma vivax [47] that cause AAT in an area of about 16 000 km 2 in the north eastern parts of the KwaZulu-Natal Province [8,9]. Because of the limited options available for controlling the parasite, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…We used mean survival time (MST) of mice post-infection as the main indicator of virulence as previously reported [23,30]; [24] and observed that the Tbr isolates were well distributed among the four virulence classes. This finding explains why clinical syndromes in HAT patients differ significantly even in a single HAT focus, thus complicating HAT diagnosis.…”
Section: Discussionmentioning
confidence: 99%